Expanding Economic Base Theory to informal and non-monetary income: Evidence from the State of Bahia, Brazil - Milano, Ludovica; Talandier, Magali (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2025)
In this paper, we discuss an operational framework to quantify and analyze regional economic development through the application of economic base theory. This theory asserts that regional development hinges not only on capturing income from outside the region (the basic sector), but also on the region’s ability to retain this income and circulate it locally for community benefit (in the non-basic sector). Our study focuses on Bahia, the largest state in Brazil’s Northeast Region, with a particular emphasis on its regiões geográficas imediatas (commuting zones). The study’s original contribution is to apply the economic base model in a Global South context using income data rather than employment data as a proxy. The available Brazilian data allow us to include in our analysis income flows that are generally overlooked in mainstream economics and entirely omitted from applications of this theory in the Global North. The findings underscore the pivotal role of informality, non-monetary income, and transfers, prompting further examination of regional income and its diverse sources in economic development analysis. Based on our results, we argue for a broader understanding of territorial economies as complex systems of socially embedded practices. This perspective calls for regional studies to shift away from the prevailing productivist viewpoint and toward a more holistic approach that embraces the diversity and richness of territorial economies.